S tudies on the phase transitions and properties of tungsten (VI) oxide nanoparticles by X - Ray diffraction (XRD) and thermal analysis - S.F. Abdullah; S. Radiman; M.A. Abdul Hamid; N.B. Ibrahim (ASEAN Journal on Science and Technology for Development, 2010)
Tungsten (VI) oxide, WO3nanoparticles were synthesized by colloidal gas aphrons(CGAs) technique.The resultant WO3nanoparticleswere characterized by thermogravimetric-differential thermal analysis (TG-DTA) and X-Ray diffraction (XRD) measurements in order to determine the phase transitions, the crystallinity and the size of theWO3nanoparticles. As a comparison, transmission electron microscope (TEM) was used to investigate the size of the WO3nanoparticles. The result from XRD and DTA show that the formation of polymorphsWO3nanoparticles have the following sequence: orthorhombic (b-WO3)®monoclinic (g-WO3) ®triclinic (d-WO3) ®monoclinic (e-WO3) with respect to the calcination temperature of 400, 500, 600 and 700°C. No diffraction peaks were found in the X-Ray diffraction measurements for the sample heat treated at 300°C (as-prepared), suggesting that an amorphous structure was obtained at this temperature whereas the crystallinity had been obtained by the other samples of theWO3nanoparticles at the calcination temperatures of 400, 500, 600 and 700°C. It is also found that the X-Ray diffraction measurements produced an average diameter of (30 ±5), (50 ±5), (150 ±10) and (200 ±10) nm at calcination temperatures of 400, 500, 600 and 700°C respectively by using Debye-Scherrer formula. The TG curve revealed that the WO3nanoparticles is purely anhydrous since the weight loss is insignificant (0.3 –1.4) % from 30 until 600°C for the WO3nanoparticles calcined at 400°C. Finally, the composition and the purity of the WO3nanoparticleshave been examined by X-Ray photoelectron spectroscopy (XPS). Theresults indicate no significant changes to the composition and the purity of the WO3nanoparticle produced due to the temperature variations